2009
DOI: 10.1182/blood-2008-12-192203
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive in vivo imaging of CD4 cells in simian-human immunodeficiency virus (SHIV)–infected nonhuman primates

Abstract: Since the earliest days of the HIV epidemic, the number of CD4 ؉ T cells per unit volume of blood has been recognized as a major prognostic factor for the development of AIDS in persons with HIV infection. It has also been generally accepted that approximately 2% of total body lymphocytes circulate in the blood. In the present study, we have used a nondepleting humanized anti-CD4 monoclonal antibody labeled with the gamma emitter indium-111 to visualize the CD4 ؉ T-cell pool in vivo in nonhuman primates with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 28 publications
(47 reference statements)
2
62
0
Order By: Relevance
“…The percentage of the labeled fragment bound to cells was .60% at 4 3 10 6 MT4 cells, and its immunoreactivity was estimated to be ;100% extrapolated under condition of excess receptor concentration based on the Lindmo method, 8 similar to the intact anti-CD4 mAbs previously described. 4 In order to demonstrate the specificity of radiotracer binding to CD4 In-DTPA-CDR-OKT4A/huIgG4. 4,9 The size-exclusion HPLC analysis of the plasma at baseline imaging showed that ;90% of the injected 99m Tc -F(ab9)2-CD4R1 remained at ;4 hours postinjection in vivo, and no evidence of formation of metabolites or catabolites, thus confirming the stability of the radiotracer in vivo (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The percentage of the labeled fragment bound to cells was .60% at 4 3 10 6 MT4 cells, and its immunoreactivity was estimated to be ;100% extrapolated under condition of excess receptor concentration based on the Lindmo method, 8 similar to the intact anti-CD4 mAbs previously described. 4 In order to demonstrate the specificity of radiotracer binding to CD4 In-DTPA-CDR-OKT4A/huIgG4. 4,9 The size-exclusion HPLC analysis of the plasma at baseline imaging showed that ;90% of the injected 99m Tc -F(ab9)2-CD4R1 remained at ;4 hours postinjection in vivo, and no evidence of formation of metabolites or catabolites, thus confirming the stability of the radiotracer in vivo (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…4 In order to demonstrate the specificity of radiotracer binding to CD4 In-DTPA-CDR-OKT4A/huIgG4. 4,9 The size-exclusion HPLC analysis of the plasma at baseline imaging showed that ;90% of the injected 99m Tc -F(ab9)2-CD4R1 remained at ;4 hours postinjection in vivo, and no evidence of formation of metabolites or catabolites, thus confirming the stability of the radiotracer in vivo (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with PET-CT, MRI can provide higher spatial resolution at near-cellular level, but with much lower sensitivity (Lecchi et al, 2007). Previous efforts using MRI in HIV research were mostly focused on imaging the pathogenesis caused by HIV or simian immunodeficiency virus (SIV) infection in the brain of patients or experimental non-human primates (Archibald et al, 2004;Di Mascio et al, 2009;Venneti et al, 2008;Zhang & Li, 2013).…”
Section: Introductionmentioning
confidence: 99%